Three-station magnetometer experiment at Antarctica during Jan-1996 to determine the velocity of disturbed-time overload auroral current systems - Dhar, Ajay; Patil, A.; Sankaran, S.; Rajaram, G. (1999)
Three fluxgate magnetometers were operated simultaneously at the Antarctic locations Maitri (70°45' S lat., 11'45' E Dakshin Gangotri (70'08' S lat., 12°E long.) and Orvin Mountains (71'56.20' S lat., 08'45.79' E long.) in Jan 1946. The three stations form the vertices of a triangle with sides ranging from 76 km to 233 km. Using appropriate electronic titters to retain pulsation's with periods between 30 sec (f= 33 MHz) and 3000 sec (f= 0.33 MHz), pulsations in X, Y and Z components of the geomagnetic field were recorded. Pulsations during disturbed conditions are interpreted in terms of the mobile auroral current systems which drift over the stations and leave signatures in ground based magnetometers. From the time-tags in similar pulsations at the three stations, the drift velocities of the overhead small-scale ionospheric current systems are estimated. The values during Jan 1996 are found to lie between 0,94 km/sec and 3,44 km/sec, and these tally well with observations of 0.6 to 2 km/sec made for the northern auroral hemisphere.